"His tummy's only tiny" – Scientific feeding advice versus women's knowledge. Women's experiences of feeding their late preterm babies. (February 2019) - Cescutti-Butler, Luisa; Hemingway, Ann; Hewitt-Taylor, Jaqui
Abstract: Objective: This paper reports on one element of a study exploring the experiences of women who are caring for late preterm baby/babies (LPBs) and focuses on their experiences of breastfeeding. Design: As this study aimed to privilege women's experiences, a feminist approach was utilised, with individual qualitative interviews in two phases conducted with a purposefully selected sample of women who were caring for a late preterm baby or babies. Template Analysis linked to Birth Territory Theory (BTT) was used to identify key issues and experiences of women. Setting and participants: Women ( N = 24 to N = 14) were recruited from an NHS Trust Hospital in the South West region of England. Findings: Infant feeding was planned with alarm clock precision. Babies, whether breast or formula fed, were subject to strict feeding guidelines/supplementation/volumes dictated by doctors and enforced by nurses and midwives and greatly impacted on women's experiences of caring. Women were powerless at times to influence feeding and regimes did not facilitate instinctive mother-care or enable babies to demonstrate innate feeding behaviours (such as rooting and early feeding cues). Key conclusions and implications for practice: The current approach to caring for women and their late PTBs tends to result in feeding becoming a source of stress and anxiety for women, rather than a positive experience. To resolve this, staff caring for women who have LPBs should focus on supporting women to trust their instincts, and to guide them in developing confidence in their ability to read their babies' cues, rather than in focusing on strict regimes of feeding. This should include individualised consideration of whether supplementation is required in the early days